A study on puffing and micro-explosion characteristics of diesel/ethanol/tetrahydrofuran blend fuel droplets - Wang, Zhen; Hu, Yong; Jiang, Yong; Cheng, Cheng; Qiu, Rong; Gutheil, Eva (Energy sources. A, Recovery, utilization, and environmental effects, 2023)
Tetrahydrofuran (THF) is a biofuel that can be added to improve the solubility of ethanol in diesel. To explore the effect of surfactants, the puffing and micro-explosion characteristics of ethanol diesel/THF (DTE) blend droplets are investigated experimentally in comparison to a counterpart blend of ethanol diesel/biodiesel (DBE). Results show that with a rise in temperature, the puffing delay time decreases rapidly opposite to the fluctuation ratio; however, the puffing delay time rises with the ethanol content, whereas the fluctuation ratio remains about constant. Moreover, the tetrahydrofuran mainly participates in the early evaporation stage resulting in more prone to the edge mode for DTE droplets, which is in contrast to the DBE droplets, which prefer the inner mode. The micro-explosion strength of DTE droplets is lower than that of DBE due to the more likely occurrence of the edge mode, but the corresponding growth rate of DTE (15.2%, 25.4%, and 56.8%) with temperatures of 573 K, 623 K, and 723 K is higher than that of DBE droplets (8.8%, 20.4%, and 48.7%). A numerical model is also established for the present blend droplets, and the simulations reveal that the THF may additionally influence the heat absorption by the liquid and hence the superheat point of ethanol, which is responsible for the bubble formation and the micro-explosion.